Socialization the Impact of Social Media on Mental Health for High School Students in Dobo City. - Marsiline Pieter; Jhoni M Tahapary (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
Social media has become an integral part of the lives of teenagers, especially among high school students. Excessive use of social media can have negative impacts on students' mental health, such as anxiety, depression, and decreased self-esteem. In Dobo City, the lack of socialization regarding the negative impacts of social media on students' mental health has created a need for a community service program aimed at raising students' awareness of these effects. This program involves various methods such as workshops, group discussions, and counseling sessions to provide knowledge on how to use social media in a healthy way. The program also offers students the opportunity to share experiences and develop skills in managing stress and improving their mental health. The results of this program show an increased awareness among students regarding the negative effects of social media and the importance of managing online time wisely. This program has also led to positive changes in students' mindset towards healthier social media use. It is hoped that the outcomes of this activity can make a positive contribution to improving students' mental health and cultivating more responsible social media habits.